1982
DOI: 10.1007/bf00498510
|View full text |Cite
|
Sign up to set email alerts
|

A three-state model of the benzodiazepine receptor explains the interactions between the benzodiazepine antagonist Ro 15-1788, benzodiazepine tranquilizers, ?-carbolines, and phenobarbitone

Abstract: The potent benzodiazepine receptor ligands beta-carboline-3-carboxylic acid ethyl ester (beta-CCE) and the corresponding methylester (beta-CCM) administered i.v. depressed segmental dorsal root potentials in spinal cats, reversed the prolongation of dorsal root potentials by phenobarbitone, and abolished the depression of a motor performance task induced by phenobarbitone in mice; beta-CCE enhanced the low-frequency facilitation of pyramidal population spikes in the hippocampus of anaesthetized rats. These eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…the 1-carbolines (Nutt et al, 1982a). In order to distinguish these two types the first group have come to be known as 'inverse agonists' (Polc et al, 1982) or 'contragonists' (Nutt, 1983) and the second group as conventional or 'neutral' antagonists. One of the contragonists, FG 7142, which is proconvulsant (Petersen et al, 1983) and anxiogenic in animals File & Pellow, 1984) has been shown in man to produce severe anxiety and panic (Dorow et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…the 1-carbolines (Nutt et al, 1982a). In order to distinguish these two types the first group have come to be known as 'inverse agonists' (Polc et al, 1982) or 'contragonists' (Nutt, 1983) and the second group as conventional or 'neutral' antagonists. One of the contragonists, FG 7142, which is proconvulsant (Petersen et al, 1983) and anxiogenic in animals File & Pellow, 1984) has been shown in man to produce severe anxiety and panic (Dorow et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Benzodiazepine receptor ligands showed the expected profile. Diazepam potentiated head-twitching (as reported by Nakamura & Fukushima, 1977) and the 'inverse agonist' PCCE (Polc et al, 1982) inhibited it. Rol 5-1788 is a benzodiazepine with antagonistic effects against both classic benzodiazepines and 'inverse agonists' (Hunkeler et al, 1981).…”
Section: Discussionmentioning
confidence: 59%
“…8-Carbolines have been purported to act as inverse agonists with regard to BZP receptors (12) since it has been evidenced to bind to these receptors (9,11), to reverse BZP action (9-11, 16, 17) and to be antagonized by a BZP antagonist, Ro 15 1788 (18,19). Therefore, l3-carbolines and BZP are expected to have a certain common feature from the structural point of view on the binding to the BZP receptor.…”
Section: Discussionmentioning
confidence: 99%